Seismic coal exploration - Dresen, L. (Handbook of geophysical exploration. Seismic exploration, 1994)
The efficient mining of hard coal in deep coal mines using highly mechanized longwall techniques requires information on the geological structure ahead of the operating face. Even minor tectonic faults with throws of only a few metres mean a loss in productivity, as they present severe working problems for underground mining equipment. Because investment costs to install a mechanized face are high, "insurance" in the form of spare capacity by both machine shifts or spare faces is uneconomic. Thus, to reduce mining costs it is essential to delineate the geology prior to mining. Today, the only effective geophysical tool to detect and to map minor faults in front of the coal cutter is in-seam seismics using channel, or so called seam waves. The techniques are well established and successfully applied for more than two decades. In-Seam Seismics covers the entire range of elementary and advanced topics in mathematics, physics and data processing of dispersive channel waves. The results of analogue and numerical modelling provide a thorough understanding of transmission, reflection, recording and interpretation of seam waves and coal seam disturbances. Fire damp proof instrumentation, target orientated underground layouts, processing and interpretation of real data impart the state-of-the-art of in-seam seismics. Selected and well-rounded case histories complete the presentation of in-seam seismics. They can help the mining engineer to come to a decision to plan and to apply in-seam seismics in case of underground mining problems. A clear text, only formulae which are necessary, many carefully designed figures, an extended list of references and a lucid index make it easy for the reader to get acquainted with seam waves or to promote the technique of in-seam seismics